Digital Preservation of Information Resources: Problems and Prospects: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Due to technological invasion digital preservation has become the important process in information society to have the long term access of information and to keep it for the future generations for their use. This paper discusses the meaning, importance, objective and strategy of digital preservation and highlights various aspects of digital preservation.